Concept of a tunable source of coherent THz radiation driven by a plasma modulated electron beam - Zhang, H; Konoplev, I; Doucas, G; Smith, J (AIP Publishing, 2018)
We have carried out numerical studies which consider the modulation of a picosecond long relativistic electron beam in a plasma channel and the generation of a micro-bunched train. The subsequent propagation of the micro-bunched beam in the vacuum area was also investigated. The same numerical model was then used to simulate the radiation arising from the interaction of the micro-bunched beam with a metallic grating. The dependence of the radiation spectrum on the parameters of the micro-bunched beam has been studied and the tunability of the radiation by the variation of the micro-bunch spacing has been demonstrated. The micro-bunch spacing can be changed easily by altering the plasma density without changing the beam energy or current. Using the results of these studies, we develop a conceptual design of a tunable source of coherent terahertz (THz) radiation driven by a plasma modulated beam. Such a source would be a potential and useful alternative to conventional vacuum THz tubes and THz free-electron laser sources.